Free Convection in Heat Transfer Flow over a Moving Sheet in Alumina Water Nanofluid - Padam Singh; Manoj Kumar (Journal of Engineering)
The present paper deals with study of free convection in two-dimensional magnetohydrodynamic (MHD) boundary layer flow of an incompressible, viscous, electrically conducting, and steady nanofluid. The governing equations representing fluid flow are transformed into a set of simultaneous ordinary differential equations by using appropriate similarity transformation. The equations thus obtained have been solved numerically using adaptive Runge-Kutta method with shooting technique. The effects of physical parameters like magnetic parameter, temperature buoyancy parameter on relative velocity and temperature distribution profile, shear stress profile, and temperature gradient profile were depicted graphically and analyzed. Significant changes were observed due to these parameters in velocity and temperature profiles.